Biomedical Consideration in the Manufacture, Clinical Trial and Bioequivalence Studies of Pharmaceuticals (Bangladesh Journal of Bioethics, 2012)
Bangladesh pharmaceutical sector has been growing at a remarkable speed since 1982. From the meager 30% national market share, now it is supplying 97% of our annual demand. Around 1,100 generics are now available in a total of around 12,000 trade name products. The national market size has crossed 6,000 crore taka per annum, where the local multinational share is only 7%. Our industries are now exporting drugs to 72 countries. But just because our pharmaceutical sector has developed its own backbone does not meant that our pharmaceutical industries have solved the relevant bioethical questions. There are complaints that some companies do not pursue necessary bioethical norm as at various levels of its manufacturing processes. Still a good number of small companies sell sub-standard and counterfeit drugs, and yet some are not following accepted GMP standards. Moreover, for capturing foreign markets we need clinical trials and bioequivalence study results. These study needs human subjects as volunteers. In a poverty-stricken country like us, if we do not establish these clinical trial and bioequivalence norms, everything becomes irrelevant. If we can establish theses norms, this could be the beginning of a new era for further growth of our pharmaceutical industries vis-à-vis our public health national economy.DOI: http://dx.doi.org/10.3329/bioethics.v2i1.9813  Bangladesh Journal of Bioethics 2011; 2(1): 18-21